Building Sustainable Kidney Transplant Programs in Developing Countries: Current Challenges and Future Directions - Sami-Ur-Rahman, Ubaid Ur Rahman, Sajid Malik, Arshad Mahmood, Saifullah, Muhammad Mubbashar Nazar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate clinical, operational, financial, ethical, and follow-up-related factors that influence the sustainability of a kidney transplant program in a developing-country hospital setting. Study Design: Retrospective single-centre observational program evaluation, supported by a focused narrative discussion of relevant transplant literature. Place and Duration of Study: Begum Akhtar Rukhsana Memorial Trust and Safari Hospital, Rawalpindi, Pakistan, from June 2022 to June 2023. Methodology: Hospital transplant records for 87 adult kidney transplant recipients were reviewed. Recipient demographics, comorbidities, perioperative resource indicators, early complications, follow-up attendance, immunosuppressive therapy adherence, financial support needs, and ethical-governance processes were extracted. Early deaths, if present, were retained as outcomes rather than excluded. Because the sample was small and aggregate data were available, findings were analysed descriptively and interpreted as a program evaluation rather than as a powered hypothesis-testing study. Results: The mean recipient age was 42.5 +/- 11.2 years and 60% were male. Hypertension and diabetes were common comorbidities. Confirmed living-donor transplantation accounted for most verifiable donor-source records. Ten donor-source entries required official external verification and were therefore not presented as confirmed deceased-donor activity. Key sustainability barriers included limited ICU/dialysis backup, staff shortages, high immunosuppressive medicine costs, missed follow-up, inconsistent adherence, ethical oversight demands, and weak deceased-donor infrastructure at the wider system level. Conclusion: Sustainable kidney transplantation in developing countries requires more than operative capacity. A durable program needs multidisciplinary staffing, reliable perioperative support, affordable lifelong immunosuppression, structured follow-up systems, transparent donor governance, and verifiable reporting of donor-source data. Keywords: Kidney transplantation; developing countries; program evaluation; living donation; transplant ethics; immunosuppression; Pakistan.